Research progress on complications of Brucellosis - Jin, Min; Fan, Zixu; Gao, Ruifang; Li, Xingnan; Gao, Zhixiang; Wang, Zhanli (Frontiers in Cellular and Infection Microbiology, 2023)
Brucellosis is a common zoonotic disease that is widely spread worldwide and poses a major threat to human health. Clinically, it often presents with non-specific symptoms such as fever, excessive sweating, malaise, myalgia, arthralgia, loss of appetite, weight loss, and enlarged liver, spleen and lymph nodes. The disease has a long and recurrent course, often accumulating in multiple systems and organs. Of these, osteoarticular involvement is the most common complication, with a prevalence of approximately 2-77%, usually manifesting as spondylitis, sacroiliac arthritis and peripheral arthritis. Hepatosplenomegaly is seen in about 50% of patients with brucellosis, and gastrointestinal disturbances such as abdominal pain, nausea, and vomiting are common. Although respiratory involvement is less common, pneumonia, pleurisy, pleural effusion, and pulmonary nodules have been reported. Besides, approximately 2-20% of cases involve infections of the male genitourinary system, mainly manifesting as unilateral epididymal-orchitis and orchitis. The most serious complication facing brucellosis is cardiovascular involvement, and although the overall mortality rate of brucellosis is about 1% and the incidence of brucellosis endocarditis is less than 2%, more than 80% of deaths are associated with endocarditis. Furthermore, brucellosis is complicated by hematologic disease, with anemia occurring in approximately 20-53% of children during the acute phase. In addition, the neurological incidence of brucellosis is about 0.5-25%, mainly manifested as meningitis. In this study, we review the multisystem complications of brucellosis with the aim of improving early diagnosis, timely treatment and prevention of long-term complications.